Implementasi Nilai-Nilai Akhlak Tasawuf melalui Hadist dalam Pembentukan Karakter Siswa di Madrasah Ibtidaiyah - Rahayu, Nur Diana; Sufiatin, Nur Lina; Choiriyah, Ma’rifatul; Habibullah, M. Romadlon (Prodi PGMI STAI Al-Akbar Surabaya, 2024)
This article discusses the implementation of Sufism moral values through hadith in character building of students in Madrasah Ibtidaiyah (MI). This study aims to identify Sufism moral values that are relevant for MI students, analyze the influence of hadith in character education, and explore how to implement them in learning. The method used in this study is a literature study by reviewing various sources on Sufism morals and their application through the hadith of the Prophet Muhammad SAW. The results of the study show that Sufism moral values such as patience, sincerity, tawakkal, and self-confidence have great relevance in character building of MI students. The hadiths of the Prophet that teach about these noble qualities can be used as a foundation in the character education process. The application of these hadiths in learning at MI not only enriches students' knowledge, but also helps shape their morals and ethics, making them more disciplined, empathetic, and have a positive attitude in everyday life. Character education based on Sufism morals provides a strong moral foundation for students in facing various challenges in life. Therefore, the implementation of the moral values of Sufism through the hadith needs to be applied more widely in MI to ensure that students not only excel in academic aspects but also in the formation of noble character. Sufism education through the hadith is very important in the formation of the character of MI students, which not only focuses on academic intelligence, but also morality and noble morals.